Nurses’ care, doctors’ cure and patients’ gratification: therapeutic relationships in medicalized motherhood practices in hospitals - Mohamad Diah, Nurazzura; Rehman, Adeela (Psychology and Education, 2021)
The aim of this study was to understand the doctor-patient-nurses relationship with respect to their therapeutic interaction build up during the treatment process. The medicalization of childbirth has remarkably changed women's experiences of the transition to motherhood. Medicalization has significant influence on women's perceptions of pregnancy and childbirth. The present study employed qualitative research design under which phenomenological inquiry was carried out. Qualitative approach was chosen as the appropriate design to explore the experiences of healthcare services from the users’ and providers’ outlook. The participants of the study comprise of 20 patients utilizing the outpatients and indoor healthcare services in PIMS and FGPC hospitals in Islamabad. To triangulate the study, the interviews were also conducted two Nursing Superintendents (one from each public hospital), six doctors (three from each hospital) including specialist consultants, medical officers and postgraduate trainee doctors. Thematic analysis technique was used to describe and interpret the information gathered from the field. The study highlighted doctor-patient interaction in three ways; instrumental, expressive and communicational. The findings also illustrated nursing care and their roles have significant impact on patients’ experiences and satisfaction with the process of care delivery and health services. It is concluded that the process of measuring healthcare services determines on whether a patient receives ample and efficient care. By highlighting women's energetic contributions to the medicalized nature of care at hospitals, motherhood is perceived as an alternative to analyses of medicalization that is inclined to outlook women either as powerless sufferers or as dynamically opposing medicalization.